POTENSI PENGGUNAAN LENIENCY PROGRAM DALAM PERKARA KARTEL INDONESIA: STUDI PERBANDINGAN LENIENCY JEPANG - M Faqih Surbakti; Anna Maria Tri Anggraini (Faculty of Law, Universitas Trisakti, 2023)
The leniency program is a pardon mechanism that allows cartel members to complain to the business competition authorities about cartel operations and receive partial or whole exemption from the penalties and/or fines that should be imposed. In Japan, the Leniency Program is in use. This article's formulation of the problem is how to create a leniency program in Japan based on the Antimonopoly Act and what are the chances of doing so to expose cartels in Indonesia's competition law system. This article offers a normative legal analysis of Indonesia's prospective use of leniency schemes in cartel proceedings. The research is descriptive-analytical in character, and data collecting through literature reviews and interviews, whereas data processing is qualitative. The findings of the research and debate indicate that it is highly likely that Indonesia will implement the leniency program by enacting the bill as the new Business Competition Law. The research's finding is that the leniency program is likely to be implemented in Indonesia by passing the bill as the country's new Business Competition Law because it is comprehensively implemented in Japan, from reporting procedures to sentencing reductions. It is suggested that Law No. 5/1999, whose provisions include a leniency program system, be amended, and that the KPPU then work with the LPSK to offer protection for reporters in the leniency program system.